2018
DOI: 10.1177/0895904818802085
|View full text |Cite
|
Sign up to set email alerts
|

Do School Discipline Policies Treat Students Fairly? Evidence From Arkansas

Abstract: It is well documented that Black students are more likely to receive expulsions and suspensions than their White peers. These disparities are troubling, but researchers and policy makers need more information to fully understand the issue. We use 3 years (2010-2011 through 2012-2013) of state-wide student- and discipline incident-level data to assess whether non-White students are receiving harsher disciplinary consequences than their White peers for similar infractions and with similar behavioral history. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Previous studies also find that minority students are exposed disproportionately to punitive institutional environments (Anderson & Ritter, 2018;Gregory & Weinstein, 2008;Kinsler, 2011;Skiba et al, 2014). Therefore, studies suggested that cross-school variation in discipline policies explain a substantial portion of the discipline gap (Anderson & Ritter, 2018).…”
Section: Racial/ethnic Discipline Gapsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies also find that minority students are exposed disproportionately to punitive institutional environments (Anderson & Ritter, 2018;Gregory & Weinstein, 2008;Kinsler, 2011;Skiba et al, 2014). Therefore, studies suggested that cross-school variation in discipline policies explain a substantial portion of the discipline gap (Anderson & Ritter, 2018).…”
Section: Racial/ethnic Discipline Gapsmentioning
confidence: 98%
“…Previous studies also find that minority students are exposed disproportionately to punitive institutional environments (Anderson & Ritter, 2018;Gregory & Weinstein, 2008;Kinsler, 2011;Skiba et al, 2014). Therefore, studies suggested that cross-school variation in discipline policies explain a substantial portion of the discipline gap (Anderson & Ritter, 2018). More recently, however, research using more extensive data and empirical approaches have found that discipline gaps persist both across and within-schools and districts (Barrett, McEachin, Mills, & Valant, 2019;Gopalan & Nelson, 2019;Owens & McLanahan, 2019).…”
Section: Racial/ethnic Discipline Gapsmentioning
confidence: 99%
“…However, other studies (e.g., Kinsler, 2011) defined racial bias as the differential treatment of Black and White students within the same school. After accounting for cross-school variation in adverse disciplinary outcomes with school fixed effects, Kinsler (2011) and Anderson and Ritter (2018) found no evidence of racial disparities within schools. We argue, however, that this approach likely underestimates the role of discrimination in the race-based discipline gap because any time-invariant structural racial discrimination at the school level will be subsumed in the school fixed effects.…”
mentioning
confidence: 91%
“…In particular, we want to know whether social support, one of the most important buffers of the strain–crime relationship (Brezina & Agnew, 2013), conditions the deleterious consequences between perceived injustice and fighting at school differently for White students and students who are racial minorities. Although Simons et al (2005) contended that “supportive control, regardless of the source or setting, reduces the probability of antisocial behavior” (995), given what we know about the greater number of (Anderson & Ritter, 2018) and qualitatively different strains (Gerlinger & Wo, 2016) that racial minorities experience, it is plausible that support processes operate differently across racial groups.…”
mentioning
confidence: 99%